Cross-Border Investment in Small International Financial Centers - Lane, Philip; Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 2010)
This note documents and assesses the role of small financial centers in the international financial system using a newly-assembled dataset. It presents estimates of the foreign asset and liability positions for a number of the most important small financial centers, and places these into context by calculating the importance of these locations in the global aggregate of cross-border investment positions. It also reports some information on bilateral cross-border investment patterns, highlighting which countries engage in financial trade with small financial centers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet